The influence of zinc electrode substrate, electrolyte flow rate and current density on zinc-nickel flow cell performance. (20th March 2021) - Trudgeon, David P.; Loh, Adeline; Ullah, Habib; Li, Xiaohong; Yufit, Vladimir; Brandon, Nigel; Liu, Maocheng; Kong, Lingbin
Abstract: This work aims to identify a suitable material for use as a zinc electrode substrate material in alkaline media, then employ this to study the effect of electrolyte flow rate and current density on zinc-nickel flow cell performance. Three metallic and four graphite composite materials are investigated, with the coulombic efficiency of zinc electrode charge / discharge cycling found to increase as hydrogen evolution onset potentials become more negative. A graphite / PVDF composite substrate demonstrates the highest coulombic efficiency at 96.7% and the most negative hydrogen evolution onset potential at -1.595 V vs. Hg/HgO. Using this material, the effect of electrolyte flow rate and current density on a zinc-nickel flow cell is investigated. Zinc morphology and flow cell performance is related to the ratio of applied current density to limiting current density. At values between 0.47 and 1, boulder type zinc morphologies occur, with smooth and compact zinc deposits resulting from current density ratios of 0.39 and below. Stable zinc-nickel flow cell performance is achieved over 200 cycles with coulombic, voltaic and energy efficiencies of 98.3, 88.1 and 86.6%, respectively, at a current density of 20 mA cm −2 .